PKM for Improving Food Security at PKK Bongan Village Tabanan District, Tabanan District-Bali Province - Anak Agung Ngurah Mayun Wirajaya; Made Sri Yuliartini; Anak Agung Made Semariyani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problems faced are that chili cultivation techniques are not yet understood, chili processing has not been carried out, equipment and materials for cultivation and chili processing are not yet complete, and the importance of strengthening organizational management. The solution is that the partner group needs to be facilitated from the technological aspects of chili cultivation, chili processing, post-harvest and processing processes, and business management of the partner group. The aim of the activity is: to increase the knowledge and skills of partners in an effort to increase food security by cultivating in the yard and utilizing chili products to be processed into processed products with high economic value which can increase people's income.